An illustrated companion to Japanese archaeology - Steinhaus, Werner; Kaner, Simon; Jinno, Megumi; Shoda, Shinya (Comparative and global perspectives on Japanese archaeology, 2020)
The Illustrated Companion to Japanese Archaeology' provides for the first time a comprehensive visual introduction to a wide range of sites and finds from the earliest occupation of the Japanese archipelago prior to 35,000 years ago to the early historical periods and the establishment of the Chinese-style capital at Heijo, modern-day Nara, in the 8th century AD. The volume originated in the largest ever exhibition of Japanese archaeological discoveries held in Germany in 2004, which brought together over 1500 exhibits from 55 lenders around Japan, and research by over 100 specialists. The Illustrated Companion brings the fruits of this project to an English-reading audience and offers an up-to-date survey of the achievements of Japanese archaeology.